1502 in Old Castile: From Mudejars to Moriscos (SP) (Edad Media. Revista de Historia, 2017)
The present work aims to cast light on a key and under-researched period in the social history of Castile and Leon: the end of the tolerated presence of Islam in this land, and the beginning of the morisco age with the coerced baptism of Muslims and their accommodation to a less tolerant society. To that end, the most recent literature has been revised and general documentation examined, along with evidence from local archives. The data analysis draws on methods close to social anthropology in an attempt to uncover possible attitudes of resistance from this subjugated community. The analysis shows that the machinery of Christian power worked to eradicate any evidence of Islamic presence, and that certain sectors of the social majority seized the opportunity to benefit from the plundering of the collective property of the aljamas. The New Christians –thenceforth known as moriscos– were able, despite their demographic and political weakness, to mount some collective resistance either by expressing their opposition to the aims of Christian power or by finding small symbolic spaces in which to preserve some of the signs of their cultural identity.
Keywords: Mudejar. Morisco. Religious Conversion. Coerced Baptism. Old Castile. Valladolid. Arévalo. Ávila.; mudejar; morisco; religious conversion; coerced baptism; Old Castile; Valladolid; Arévalo; Ávila